2013
DOI: 10.1038/eye.2012.303
|View full text |Cite
|
Sign up to set email alerts
|

Open-sky isolated subtotal Muller’s muscle resection for ptosis surgery: a review of over 300 cases and assessment of long-term outcome

Abstract: Purpose To evaluate short-and long-term success rates on isolated subtotal Muller resection in over 300 cases of ptosis over a 10-year period. Methods Clinical records were retrospectively evaluated for aetiology and severity of ptosis, levator function, response to phenylephrine, pre-and postoperative margin reflex distance of the upper lid (MRD1), postoperative lid contour and symmetry, complications and follow-up duration. Main outcome measures: change in MRD1 and eyelid contour. Surgical success: postopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 19 publications
1
17
2
3
Order By: Relevance
“…18,22,23 Varying responses to phenylephrine may have been caused by different severity of fatty degeneration of Muller's muscle and viability of its adrenergic receptors. 24 Although it would have been useful to compare the phenylephrine response-positive with the response-negative group, the sample size in this study was too small for statistically significant result. However, the principle of our technique was to allow direct visualization of the eyelid anatomy with subsequent intraoperative lid height and contour adjustments.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…18,22,23 Varying responses to phenylephrine may have been caused by different severity of fatty degeneration of Muller's muscle and viability of its adrenergic receptors. 24 Although it would have been useful to compare the phenylephrine response-positive with the response-negative group, the sample size in this study was too small for statistically significant result. However, the principle of our technique was to allow direct visualization of the eyelid anatomy with subsequent intraoperative lid height and contour adjustments.…”
Section: Discussionmentioning
confidence: 95%
“…If undercorrection was noticed in the early postoperative period, reoperation using the same technique but placing more sutures and aiming for slight intraoperative lid height overcorrection yielded successful results. Peter et al 24 reported 92% of patients felt that their initial postoperative lid height was maintained over the long-term, in contrast to anterior aponeurosis surgery in which lid height tends to drop over time. The outcome of our study in the early postoperative period is encouraging, and further long-term observation is required to evaluate whether the lid height improvement could be maintained over time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations